Analyzing Social Disadvantage in Rural Peripheries in Czechia and Eastern Germany. Conceptual Model and Study Design. - Keim-Klärner; Bernard, Josef; Bischof, Susann; van Dülmen, Christoph; Klärner, Andreas; Steinführer, Annett (My University, 2021)
The aim of this Working Paper is to introduce a conceptual model and study design for researching social disadvantage in rural peripheries, focusing on the interplay of social disadvantage and spatial disadvantage. The paper presents the theoretical concepts, understandings and definitions, as well as the research design the authors draw on in the international research project ‘Social disadvantage in rural peripheries in Czechia and eastern Germany: opportunity structures and individual agency in a comparative perspective. The project investigates the multifaceted relationships between social disadvantage, local and regional opportunity structures and individual agency in rural peripheries in Czechia and eastern Germany from a comparative perspective. It focuseson two sets of research questions. The first set concerns the quantitative patterns of social disadvantage and spatial disadvantage in rural areas. The second set asks about the impact of opportunity structures as part of the residential context on particularly disadvantaged groups in four case study regions. The project applies theories of peripheralization and rural restructuring, and considers social networks and individual agency. Area-level secondary data and accessibility analyses and qualitative case studies, including ego-centered network analyses and GPS mapping of time-space activity patterns, are used.
Keywords: Ländlicher Raum; Periphere Region; Problemraum; Benachteiligung; Soziale Ungleichheit; Regionale Disparität; Empirische Untersuchung; Konzeption; Raumwissenschaft